Defining brokers, intermediaries, and boundary spanners: a systematic review. (20th February 2022) - Neal, Jennifer Watling; Neal, Zachary P.; Brutzman, Brian
Abstract : Background: A growing literature focuses on the roles of brokers, intermediaries, and boundary spanners (BIBS) in addressing the challenges of transferring research evidence between the research and practice or policy communities. Aims and objectives: In this systematic review, we examined two research questions: (1) where, how, and when are different BIBS terms (broker, intermediary, and boundary spanner) used? and (2) which BIBS terms get defined, and when these terms are defined, who are BIBS and what do they do? Methods: We conducted literature searches designed to capture articles on BIBS and the transfer of research evidence. We extracted information about eligible articles' characteristics, use of BIBS terms, and definitions of BIBS terms. Findings: The search revealed an initial pool of 667 results, of which 277 articles were included after screening. Although we coded 430 separate uses of BIBS terms, only 37.2% of these uses provided explicit definitions. The terms, 'broker' and 'brokerage', were commonly applied in the health sector to describe a person engaged in multiple functions. The term, 'intermediary', was commonly applied in the education sector to describe an organisation engaged in dissemination. Finally, the terms 'boundary spanner' and 'boundary spanning' were commonly applied in the environment sector to describe people or organisations that engage in relationship building. Discussion and conclusions: Results demonstrated that when BIBS were defined, there were important (albeit implicit) distinctions between terms. Based on these results, we identify archetypal definitions for brokers, intermediaries, and boundary spanners and offer recommendations for future research.